Modulação do sistema glutamatérgico em plaquetas: efeito de metais pesados e organocalcogênios - Borges, Vanessa Corralo (2007)
Research strategies have been developed to characterize parameters in peripheral tissues that might easily be measured in humans as surrogate markers of damage, dysfunction or interactions involving neural targets of toxicants. Human platelets have been repeatedly suggested as an excellent model for various aspects of the synaptic apparatus and these cells have been shown to accumulate glutamate in a manner similar to that in as synaptosomal preparations. In fact, blood cells such as platelets are ideally suited for monitoring a chemical s neurotoxic effects because of their easy accessibility and because they share a number of functions similar to those of central nervous system neurons. The increasing number of chemicals present in the habitational and occupational environment elevates the risk of toxic human exposure. Heavy metals have become one of many contaminants found in our environment. These metals may react with free protein cysteine thiol groups, which are involved in the function of many enzymes, structural proteins and receptors. Organoselenium (diphenyl diselenide and ebselen) and organotellurium (diphenyl ditelluride) are known to disturb cellular functions by oxidizing -SH groups of biomolecules. Considering that -SH groups are important constituents of receptors and transporters, the effects of heavy metals (Hg2+, Pb2+and Cd2+) as well as diphenyl diselenide, diphenyl ditelluride and ebselen on glutamatergic system in human platelets were examined. The results clearly demonstrated that Hg2+, Cd2+ and Pb2+ inhibited [3H]-glutamate uptake in human platelets. Hg2+ inhibited [3H]-glutamate binding, while Cd2+ and Pb2+ stimulated [3H]-glutamate binding in human platelets. Heavy metals caused an increase on lipid peroxidation and reactive oxygen species measurement in platelets, suggesting that oxidative stress, at least in part, could be one of the mechanisms involved in heavy metals-induced neurotoxicity. The use of 2,3-dimercaptopropanol (BAL), a dithiol chelating agent therapeutically used for the treatment of heavy metals poisoning, was able to protect and restoring [3H]-glutamate binding against effects caused by Pb2+, Cd2+ and Hg2+. 2,3 dimercaptopropane-1-sulfonic acid (DMPS), another dithiol chelating agent, was able protecting and restoring against the effects caused by heavy metals in [3H]-glutamate binding in platelets. Similar results were obtained with ditiothreitol (DTT), a sulfhydryl agent commonly used as a -SH groups reductor. The dithiol agents alone did not alter [3H]-glutamate binding. In contrast, reduced glutathione (GSH), a monothiol reducing agent, inhibited [3H]-glutamate binding in all tested concentrations. In addition, this compound did not protect the effect caused by heavy metals. These results suggest that dithiol agents (BAL, DMPS and DTT) could act by chelating heavy metals or/and by reducing SH groups of glutamatergic receptors. Diphenyl diselenide and diphenyl ditelluride inhibited [3H]-glutamate binding, but ebselen did not alter this parameter. All organochalcogens tested inhibited [3H]-glutamate uptake in human platelets. The inhibition caused by organochalcogens in glutamatergic system, was not recovered by the addition of reducing agents (DTT and GSH), indicating that toxicological properties of these compounds an not exclusively related to oxidation of SH groups. Considering the results obtained, could be suggested that platelets to be a suitable biomarker for exposure by toxic compounds and represented a good model for investigated the mechanism involved in changes caused by these compounds.